’iktišāf madfan ya‘ūdu li-‘aṣri ’l-burūnzi ’l-qadīmi fī Sarāqib - Sulaymān, ’Anṭuwān
so im Sommaire de la partie arabe; p. 93 jedoch ?rytsnkw geschrieben; Discovery of an Old (i.e. Early) Bronze Age Burial Ground at Sar?qib; ersch. 1986; Arabic section; in Arabic.